THE EFFECTIVENESS OF DIGITAL COMICS IN IMPROVING INDUSTRIAL REVOLUTION SKILLS AND STUDENT MOTIVATION - Kristin Sangur; Audrey Makatita (EDU SCIENCES JOURNAL, 2021)
Digital comics are media that support the learning process in the 4.0 era. Digital comics contain the concept of bacteria that is easy for students to understand. The purpose of this study was to analyze the increase in problem-solving skills, critical thinking, and student motivation in learning the concept of bacteria using digital comics. The subjects in this study were 26 third semesters’ students of the biology education program. The comics that are used are digital comics created by researchers using the comic life application. The instruments used were critical thinking test questions and problem-solving and motivation questionnaires. Data analyses were done by using descriptive analysis techniques. The results of the t-test analysis showed that there were differences in students' problem solving and critical thinking abilities before and after learning using digital comics "Bacterial Characteristics" (p <0.05). Meanwhile, student motivation also has differences between the first meeting and the second meeting during learning using digital comics (p <0.05). The use of digital comics can empower students' problem-solving skills, critical thinking, and motivation in learning the concept of bacterial characteristics